2020
DOI: 10.1186/s13020-020-00340-y
|View full text |Cite
|
Sign up to set email alerts
|

RalB degradation by dihydroartemisinin induces autophagy and IFI16/caspase-1 inflammasome depression in the human laryngeal squamous cell carcinoma

Abstract: Background: Interferon-inducible 16 (IFI16)/caspase-1 inflammasome activates and secretes IL-1β. However, it is still unclear whether the IFI16 inflammasome is involved in human laryngeal squamous cell carcinoma. Autophagy directly removed inflammasome components and limited early IL-1β production. RalB is required for the crosstalk between inflammasome and autophagy in macrophages. Dihydroartemisinin (DHA), the main derived ingredient of artemisinin, has a variety of biological activities. The mechanism of DH… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…It was previously reported that DHA exerted an effect in multiple diseases, including fibrosis. 8 , 26 , 27 In the present study, DHA inhibited the TGF-β-induced fibrosis of HTFs following glaucoma surgery by inducing autophagy. To the best of our knowledge, the present study was the first to determine the function of DHA in the formation of HS.…”
Section: Discussionsupporting
confidence: 56%
“…It was previously reported that DHA exerted an effect in multiple diseases, including fibrosis. 8 , 26 , 27 In the present study, DHA inhibited the TGF-β-induced fibrosis of HTFs following glaucoma surgery by inducing autophagy. To the best of our knowledge, the present study was the first to determine the function of DHA in the formation of HS.…”
Section: Discussionsupporting
confidence: 56%
“…In addition to inducing apoptosis, DHA also has the ability to induce autophagy in tumors (22,41,69,77,81). When DHA damages tumor cells, autophagy is activated to clear damaged organelles, but excessive autophagy often leads to cell death.…”
Section: Autophagymentioning
confidence: 99%
“…Activation involves Ca 2+ binding and GFL‐GFR recognition, culminating in homodimerization, autophosphorylation, and downstream signaling activation [66] . This influences multiple pathways, including PI3K/AKT, RAS/RAF/MEK/ERK, JAK2/STAT3, and PLC‐γ, impacting cell proliferation, survival, and differentiation [67] . Aberrations in RET and overexpression are discerned across a wide array of cancers, including breast, pancreatic, colorectal, melanoma, lung, and prostate cancers, contributing to tumor proliferation, invasion, and migration [68] .…”
Section: Pyridinementioning
confidence: 99%
“…[66] This influences multiple pathways, including PI3K/AKT, RAS/RAF/MEK/ERK, JAK2/STAT3, and PLC-γ, impacting cell proliferation, survival, and differentiation. [67] Aberrations in RET and overexpression are discerned across a wide array of cancers, including breast, pancreatic, colorectal, melanoma, lung, and prostate cancers, contributing to tumor proliferation, invasion, and migration. [68] Tyrosine kinase inhibitors, particularly multikinase inhibitors, emerge as promising strategies targeting RET-driven diseases.…”
Section: Rearranged During Transfection (Ret) Inhibitorsmentioning
confidence: 99%